2009
DOI: 10.1167/iovs.08-3031
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoid EP4Receptor Stimulation Produces Ocular Hypotension by a Mechanism That Does Not Appear to Involve Uveoscleral Outflow

Abstract: The EP(4) receptor agonist 3,7-dithia PGE(1) is a highly efficacious IOP-lowering drug in monkeys. It has no effect on uveoscleral outflow but does increase total outflow facility, which accounts for a substantial proportion of the ocular hypotensive activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 37 publications
2
32
0
1
Order By: Relevance
“…Hori et al (2009) reported that local EP4 agonist treatment improved noise-induced hearing loss in guinea pigs. Finally, Woodward et al (2009) reported that an EP4 receptor agonist potently decreased intraocular pressure in laser-induced ocular hypertensive monkeys. EP4 could potentially be a new therapeutic target for antiglaucoma therapy.…”
Section: K Other Systemsmentioning
confidence: 99%
“…Hori et al (2009) reported that local EP4 agonist treatment improved noise-induced hearing loss in guinea pigs. Finally, Woodward et al (2009) reported that an EP4 receptor agonist potently decreased intraocular pressure in laser-induced ocular hypertensive monkeys. EP4 could potentially be a new therapeutic target for antiglaucoma therapy.…”
Section: K Other Systemsmentioning
confidence: 99%
“…Laser-induced ocular hypertension in monkeys was used, as previously described (Woodward et al, 2009). Briefly, female cynomolgus monkeys, weighing 2-4 kg, were trained to accept pneumatonometry, while conscious, in customdesigned restraining chairs.…”
Section: Methodsmentioning
confidence: 99%
“…To extend the pharmacological characterization of PGE 2 -glyceryl ester to an integrated living biologic system, we used the eye for convenient noninvasive study. Intraocular pressure was recorded in these experiments, since it is well-known to be influenced by the majority of prostanoid receptors (Hoyng and de Jong, 1987;Woodward et al, 1990Woodward et al, , 1994Woodward et al, , 2009Stjernschantz and Resul, 1992;Nilsson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the unique receptor profile for each analog may induce ECM modulation via different cascade pathways. One EP4 receptor agonist in particular has been shown to induce an increase in conventional outflow facility specifically [129]. Comparisons have been made between the effects of laser treatment and prostaglandins in SC monolayer permeability.…”
Section: Traditional Topical Medications In the Management Of Glaucomamentioning
confidence: 99%
“…Furthermore, selective EP 4 agonists have also been shown to be efficacious in treatment of POAG. Both SC and TM cells express EP 4 receptors, and hypertension-lowering effects are believed to be primarily localized to the conventional pathway [129,175]. EP 4 receptors alone induce expression of early growth response factor-1, mediated by extracellular signal-regulated kinases [176], while these kinases are also known to influence MMP expression [177].…”
Section: New Classes Of Drugmentioning
confidence: 99%